The Importance of Differential Diagnosis of Complete Blood Count Abnormalities in the Early Postpartum Period: A Case Report - Abdullah Acar; Emine Acar; Canan Ünal Aydın (Women’s Health and Multidisciplinary Research, 2026)
Hematological changes during pregnancy and the puerperium are common and are often considered physiological. Mild anemia and leukocytosis are frequently encountered; however, severe or atypical abnormalities may indicate serious underlying pathologies. Acute myeloid leukemia (AML) is a rare but life-threatening condition that can present during pregnancy or the postpartum period, and its diagnosis may be delayed because of overlapping physiological changes. A 34-year-old multiparous woman (G4P4) was referred to our hospital 2 hours after vaginal delivery because of severe anemia. Laboratory evaluation revealed a hemoglobin level of 5.5 g/dL, a platelet count of 65×109/L, and a white blood cell count of 54.8×109/L. Peripheral blood smear examination demonstrated marked leukocytosis with immature myeloid cells, raising suspicion of acute leukemia. A review of the antenatal records revealed inadequate prenatal follow-up and unresolved cytopenias. Further hematological workup confirmed a diagnosis of AML with an FLT3 mutation, and chemotherapy was initiated promptly. This case highlights the importance of a meticulous differential diagnosis in pregnant and postpartum patients presenting with anemia accompanied by leukocytosis or thrombocytopenia. Peripheral blood smear examination is a simple yet indispensable diagnostic tool for the early detection of malignant hematological diseases.